(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Lead aprons are typically worn by radiographers to protect them from harmful radiation. As such, a good radiation shield must have a high Lead Equivalence to minimize the transmitted radiation dose during exposure. While most radiation shields fulfil this requirement by using matrices of lead and other substances, most aprons are uncomfortable to wear. Further, if the examination takes longer than expected, the radiographer will feel discomfort because of the heavy weight of the apron, or the smooth surface of the coated casing material. Another issue is the poor fit and design of the aprons due to the stiffness of the lead sheet. In general, the comfort characteristics of any textile material are related to air permeability, moisture management, abrasion resistance, fabric structure, thickness and weight, as well as yarn types. The objective of this study is to use standard testing methods to characterize some selected fabrics in terms of their X-ray shielding ability, physical, mechanical, and morphologic properties. The implication of this research will help for further study of this type of fabrics to improve thermal comfort of X-ray protective clothing.